All Days 1989
DOI: 10.4043/6005-ms
|View full text |Cite
|
Sign up to set email alerts
|

Scour From Cyclic Lateral Loading of Piles

Abstract: Two types of scour can be identified at piles supporting offshore structures:erosion of the sea bottom (sea-bottom scour) at obstructions due to oscillatory waves and unidirectional currents, andthe loss of soil around a pile due to the cyclic deflection of the pile under wave forces. The second type (pile scour) is associated with cohesive soils and is the subject of this study. Observations during onshore testing have revealed that the loss of lateral capacity of a pile in cohesive soils is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is possible that over time this cyclic loading may trigger a Foundation scour as a geohazard John M. Harris, Richard J.S. Whitehouse, Nicholas S. Tavouktsoglou and Pedro M. Godinho response in the local seabed soils although very few studies have been published on this potential mechanism (Reese et al, 1989;Al-Hammadi and Simons, 2016). The corresponding movement of the pile in response to loading being dependent on the resultant soil reaction.…”
Section: Scour As a Conditioning Ground Geometry And A Triggermentioning
confidence: 99%
“…It is possible that over time this cyclic loading may trigger a Foundation scour as a geohazard John M. Harris, Richard J.S. Whitehouse, Nicholas S. Tavouktsoglou and Pedro M. Godinho response in the local seabed soils although very few studies have been published on this potential mechanism (Reese et al, 1989;Al-Hammadi and Simons, 2016). The corresponding movement of the pile in response to loading being dependent on the resultant soil reaction.…”
Section: Scour As a Conditioning Ground Geometry And A Triggermentioning
confidence: 99%
“…There have been few studies published into the effect of scour development due to cyclic loading. Reese et al (1989) reported on experiments carried out to assess the impact on soil loss due to cyclic deflection of a pile under wave forces.…”
Section: Cyclic Loading Effectsmentioning
confidence: 99%
“…Several researchers have previously investigated the effect of scour formation on the lateral response characteristics of piles (Li et al, 2018;Prendergast et al, 2013). Reese et al (1989) presented an overview of the scour formation process in cohesive soils, focusing on the gap created at the soil-pile interface due to water injection induced by the cyclic loading. They concluded that this gap increases with the number of cycles, leading to a considerable decrease in lateral capacity.…”
Section: Introductionmentioning
confidence: 99%